Effect of a cryogenic treatment in the microstructure, functional and flow properties of soy protein isolate. (October 2021) - Acosta-Domínguez, Laura; Cocotle-Ronzón, Yolanda; Alamilla-Beltrán, Liliana; Hernandez-Martinez, Eliseo
Abstract: In this work, the impact of cryogenic treatment of soy protein isolate (SPI) on its microstructure, functional and flow properties was evaluated. SPI was treated with 96% ethanol, freezed in liquid nitrogen, and then lyophilized to obtain the modified soy protein isolate (MSPI). To analyze the changes in the surfaces of the SPI and MSPI particles, AFM images were taken. An adsorption isotherm was performed at 25 °C, then the surface fractal dimension and specific surface area were analyzed by water adsorption isotherm at 25 °C. Functional properties such as emulsion capacity, foam, oil and water absorption, gelling and viscosity were determined. Likewise, the flow properties of powders as bulk density, tapped density, particle density, Hausner index, compressibility index and porosity were determined. MSPI showed hollows in the surface, higher roughness (Rq) and higher specific surface area than SPI. Regarding functional properties, MSPI presented higher viscosity, oil and water absorption, emulsifying and gelling capacity than SPI. MSPI powders showed lees flowability than SPI. The results suggested that the application of a cryogenic treatment in SPI changes the microstructure and impacts on the functional and flow properties of SPI, since some functional properties were improved, such as gelation, viscosity, emulsifying, adsorption and absorption capacity; and the flow properties were modified. Graphical abstract: Image 1 Highlights: A new methodology is proposed to improve functional properties of vegetables proteins. Microstructure is modified by the cryogenic treatment. Cryogenic treatment improve the functional properties of soy protein isolate.